Spotlight on graduate student: Junaid Akhter, PhD (Industrial Chemistry) candidate - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Khairu Aidilnishah, Rizan Jalil; Mohd Asyrak, Deraman; Rajan, Jose; Aziah, Mohd Yusoff (Penerbit UMP, 2009)
Junaid Akhter, 25, was born and raised in He began his research on the"Studies on Pakistan, the youngest of 3 brothers and a sister. chemical and biotransformation of He attended secondary school at the Pakistan Air patchouli alcohol and selected Force Degree College in Risalpur. Encouraged by derivatives of Postegamon cab/in" his pharmacist father, Junaid trained as an supervised by Prof. Dr. Mashitah Mohd Organic Chemist at the Kohat University of Yusoff and co-supervised by Dr. Roziah Science & Technology and successfully defended Kambol earlier this year. The study is a Master's thesis entitled, "Cephradine Metal funded by the Fundamental Research Interactions" before being offered a place to Grant Scheme awarded to both pursue his PhD at UMP.